Tropus Grece: The Use of Greek-Texted Ordinary Chants in 10th/11th-Centuries Manuscripts from St Gall and Limoges - Wanek, Nina-Maria (Journal of the International Society for Orthodox Music, 2020)
The four ordinary chants (Gloria, Credo, Sanctus and Agnus Dei) that appear with Greek texts in Western manuscripts from the ninth century onwards and have come to been known as “Missa graeca”, still constitute one of the great mysteries in medieval liturgical chant. There are numerous hypotheses regarding the intent and use of these chants: One such hypothesis argues that the Greek-texted chants might have functioned as tropes, i.e. additions to a pre-existing chant. So far, no conclusive answer has been found to this assumption. With the help of the newest results of my current research project on the “Cultural Transfer between Byzantium and the West” the article analyses the different kinds of treatment and functions of the chants in question: Point of departure are a) the fact that in tenth/eleventh centuries-St Gall manuscripts the Greek-texted chants are incorporated in those parts of the codices, which contain tropes of the ordinary chants and b) that Aquitanian manuscripts of approx. the same time include Greek-texted chants among the tropes for Pentecost: E.g. in F-Pn lat. 909 from St Martial in Limoges, the Amnos tu theu (Agnus Dei) is called a “tropus grece” and in F-Pn lat. 1084, also from Limoges, the same chant is actually used like a trope with a cue to the “Miserere nobis”.